X-men villains - Shea, Christopher; Ruiz, Aristides; Thompson, Del.; Thompson, Dana. (New York : Random House, 1995)
Describes some of the evil characters that the X-men must face, including Magneto, the Blob, Sabertooth, and Pyro.
Keywords: X-Men (Fictitious characters) -- Fiction; Science fiction